Efficacy of sodium hypochlorite and quaternary ammonium compounds on yeasts isolated from apple juice - Brugnoni, Lorena Inés (2012)
In this work, we evaluated the effectiveness of sodium hypochlorite and a commercial quaternary ammonium compound against four wild yeast strains in their different growth forms: planktonic, sessile and forming microcolonies. These yeasts had been isolated from apple juice processing plant, and appropriate environmental conditions were employed throughout the work. For planktonic cells, 4 log reduction was obtained using the lowest concentration of sodium hypochlorite (200 ppm) on all tested strains. However, quaternary ammonium chloride was effective only on Zygosaccharomyces sp. in all in-use concentrations tested, and only the stronger in-use concentration (1:30) was effective on Rhodotorula mucilaginosa. Because of the above results, the disinfection on sessile yeast cells was performed only with sodium hypochlorite solutions. In cells attached in batch conditions, the highest concentration of sodium hypochlorite (500 ppm) was necessary to get 4 log reduction. In order to obtain a 3 log reduction on Zygosaccharomyces sp. microcolonies formed in laminar flow conditions, the combined action of 0.5% w/v NaOH and 500 ppm sodium hypochlorite was required. We concluded, thus, that cells forming microcolonies under laminar flow conditions were less susceptible to disinfectants than those suspended or attached in batch conditions. These results also indicated that attachment and colonization of autochthonous yeasts must be properly identified to evaluate the effectiveness of disinfectants used in apple juice processing plants.